Multiple Nonlinear Optical Response of Gold Decorated-Reduced Graphene Oxide-Nanocomposite for Photonic Applications - Bongu, Sudhakara Reddy; Bisht, Prem B.; Thu, Tran V.; Sandhu, Adarsh (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2015)
Multiple nonlinear optical (NLO) responses of gold nanoparticles-grafted reduced graphene oxide (Au-rGO) nanocomposite have been studied with open aperture Z-scan setup. The nanocomposite shows the effect of saturable absorption (SA) at lower intensity that flips to reverse saturable absorption (RSA) on increasing the input irradiance. The results have been explained on the basis of the Pauli-blocking and multiphoton absorption. The NLO response of the material has been compared with the electronic diode characteristics. The simulations of the NLO responses of the nanocomposite have been done by varying saturation intensity and two-photon absorption coefficient of the material.